Preoperative Blood Loss of Isolated Acetabular Fractures. Issue 3 (March 2023) - McGee, Andrew; Obinwa, Chibuike; White, Parker; Cichos, Kyle; McGwin, Gerald; Bergin, Patrick; Spitler, Clay
Abstract : Objective: To quantify preoperative blood loss in isolated acetabular fractures and identify any fracture or patient characteristics associated with increased blood loss or blood transfusion. Design: Retrospective cohort study. Setting: Two level 1 trauma centers. Patients/Participants: All patients with operative, isolated acetabular fractures from January 2010 to December 2018. Intervention: Operative management of an acetabular fracture. Main Outcome Measurements: Volume of preoperative blood loss and transfusion rates associated with isolated acetabular fracture patterns. Results: A total of 598 patients were included. The mean preoperative blood loss of all fractures was 1172.6 mL. The 3 fracture patterns with the greatest average preoperative blood loss were associated both column (1454.9 mL), T-type (1374.8 mL), and anterior column posterior hemitransverse fractures (1317.7 mL). The acetabular fracture pattern had a significant association with preoperative blood loss and preoperative transfusion. The timing from injury to surgery and body mass index were significantly associated with preoperative blood loss. Conclusions: In conclusion, operatively treated isolated acetabular fractures surprisingly lose an average of greater than 1 liter of blood in the preoperative setting. Surgeons must carefully assess patient's physiology, ensuring they are adequately resuscitated before surgery and remain aware that increasing body mass index is associated with increased preoperative blood loss. However, as patients await surgery, unreduced acetabular fractures continue to contribute to ongoing blood loss beyond the first 24 hours from injury. We believe the best hemostasis after initial resuscitation is provided by surgical reduction and fixation, and we recommend a continued early surgical intervention to prevent continued bleeding from fracture surfaces. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.